System of Recruitment of Legal Profession in a Nation of Law of Pancasila - Saiful Anam (The Indonesian Journal of International Clinical Legal Education, 2019)
The regulation of system and mechanism of recruitment of legal profession like Advocate/ Lawyer and Notary Public still has a number of weaknesses, and it also still raises some issues in Indonesia. There are still problems in the recruitment of advocates, for example, we find that there are multiple mechanisms used by advocate organizations. Some advocate organizations still implement the professional education of advocacy as the requirement for the candidates to get the exam, and there are also some advocate organizations that require the candidates to take the exam before getting the professional education. Some problems do also exist in the profession of notary public, in which the candidates should obtain Master of Public Notary. On the other side, some professional education could be implemented by non degree system, however, most of the professional educations are implemented through advanced educational systems. For example, when the candidates of notary public completed the notary school, then they will be awarded Master of Public Notary. The researcher used normative and sociological legal research method, and therefore, this research would generate the recruitment system of legal profession that is in accordance with the values and principles in the Pancasila-based Nation of Law.